A comparison of the effectiveness of three parenting programmes in improving parenting skills, parent mental-well being and children's behaviour when implemented on a large scale in community settings in 18 English local authorities: the parenting early intervention pathfinder (PEIP) - Lindsay Geoff; Strand Steve; Davis Hilton (BMC, 2011)
Abstract Background There is growing evidence that parenting programmes can improve parenting skills and thereby the behaviour of children exhibiting or at risk of developing antisocial behaviour. Given the high prevalence of childhood behaviour problems the task is to develop large scale application of effective programmes. The aim of this study was to evaluate the UK government funded implementation of the Parenting Early Intervention Pathfinder (PEIP). This involved the large scale rolling out of three programmes to parents of children 8-13 years in 18 local authorities (LAs) over a 2 year period. Methods The UK government's Department for Education allocated each programme (Incredible Years, Triple P and Strengthening Families Strengthening Communities) to six LAs which then developed systems to intervene using parenting groups. Implementation fidelity was supported by the training of group facilitators by staff of the appropriate parenting programme supplemented by supervision. Parents completed measures of parenting style, efficacy, satisfaction, and mental well-being, and also child behaviour. Results A total of 1121 parents completed pre- and post-course measures. There were significant improvements on all measures for each programme; effect sizes (Cohen's d) ranged across the programmes from 0.57 to 0.93 for parenting style; 0.33 to 0.77 for parenting satisfaction and self-efficacy; and from 0.49 to 0.88 for parental mental well-being. Effectiveness varied between programmes: Strengthening Families Strengthening Communities was significantly less effective than both the other two programmes in improving parental efficacy, satisfaction and mental well-being. Improvements in child behaviour were found for all programmes: effect sizes for reduction in conduct problems ranged from -0.44 to -0.71 across programmes, with Strengthening Families Strengthening Communities again having significantly lower reductions than Incredible Years. Conclusions Evidence-based parenting programmes can be implemented successfully on a large scale in community settings despite the lack of concentrated and sustained support available during a controlled trial.